DNase inhibits early biofilm formation in Pseudomonas aeruginosa- or Staphylococcus aureus-induced empyema models - Deng, Wusheng; Lei, Yanmei; Tang, Xiujia; Li, Dingbin; Liang, Jinhua; Luo, Jing; Liu, Liuyuan; Zhang, Wenshu; Ye, Liumei; Kong, Jinliang; Wang, Ke; Chen, Zhaoyan (Frontiers in Cellular and Infection Microbiology, 2022)
Anti-infection strategies against pleural empyema include the use of antibiotics and drainage treatments, but bacterial eradication rates remain low. A major challenge is the formation of biofilms in the pleural cavity. DNase has antibiofilm efficacy in vitro, and intrapleural therapy with DNase is recommended to treat pleural empyema, but the relevant mechanisms remain limited. Our aim was to investigate whether DNase I inhibit the early biofilm formation in Pseudomonas aeruginosa- or Staphylococcus aureus-induced empyema models. We used various assays, such as crystal violet staining, confocal laser scanning microscopy (CLSM) analysis, peptide nucleic acid-fluorescence in situ hybridization (PNA-FISH), and scanning electron microscopy (SEM) analysis. Our results suggested that DNase I significantly inhibited early biofilm formation in a dose-dependent manner, without affecting the growth of P. aeruginosa or S. aureus in vitro. CLSM analysis confirmed that DNase I decreased the biomass and thickness of both bacterial biofilms. The PNA-FISH and SEM analyses also revealed that DNase I inhibited early (24h) biofilm formation in two empyema models. Thus, the results indicated that DNase inhibited early (24h) biofilm formation in P. aeruginosa- or S. aureus-induced rabbit empyema models and showed its therapeutic potential against empyema biofilms.